Bimbingan Konseling Pendidikan terhadap Siswa Kristen Bermasalah di Sekolah Menengah Pertama Negeri 07 Belimbing - Sudarmono Sudarmono; Jerry Jerry (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2026)
Counseling etymologically derives from the noun counsel, which originates from the Latin consilium, rooted in consilere, meaning “to consult,” or to seek the views and advice of others as guidance for consideration and decision-making. As a verb, to counsel or counseling refers to the act of providing advice, guidance, warnings, encouragement, and instruction aimed at fostering self-surrender in addressing problems and managing negative behaviors among students. Educational guidance and counseling aim to strengthen Christian students to live victoriously in the Lord Jesus Christ by bringing them to an understanding of the light of God’s Word and the acceptance of themselves as God’s grace. This Classroom Action Research was conducted to address and resolve the problems of Christian students based on the research formulation, particularly through the application of intellectual, moral, and social approaches as strategic steps to enhance educational counseling services. The study employed a qualitative approach, with data collected through in-depth interviews and field notes. Data analysis was carried out by categorizing findings to generate emerging themes. In-depth interviews and focus group discussions were conducted with three teacher participants and two student participants. The findings revealed that several students required special attention due to tendencies toward delinquent behavior, while one case indicated a student’s involvement in narcotics. These findings demonstrate that student-related issues require special intervention efforts to improve their spiritual and mental well-being, leading them to a deeper knowledge of the Lord Jesus Christ as their personal Savior. The ultimate goal is the salvation of students’ souls and the glorification of the name of the Lord Jesus Christ.